Charlie’s Struggles in Crystal Maldonado’s Fat Chance, Charlie Vega - Aini, Dinera Qurrotul; Litaay, Adeline Grace M. (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2025)
This study examines the personal struggles experienced by Charlie Vega, the main character of Crystal Maldonado’s Fat Chance, Charlie Vega. The study investigates how Charlie survives the emotional and psychological challenges she faces as an obese Latina teenager. It focuses on the impact of intersecting factors—race, gender, and body image she experienced, and how these factors shape the way she responds to pressure from her environment. Using a qualitative method and psychological literary approach, the analysis categorizes Charlie’s experiences into four types of struggles as defined by Maizler (2012): negative, positive, inevitable, and chosen struggle. The findings reveal that Charlie’s life depends not only on emotional resilience, but also on strategic coping mechanisms such as writing, seeking community support, and changing her perception of herself. The study emphasizes that her struggle is not a metaphor for growth, but a real ongoing struggle for recognition and acceptance. Keywords: Body Image, Intersectionality, Race, Self-Identity, Struggles